2009
DOI: 10.1177/0192623309356450
|View full text |Cite
|
Sign up to set email alerts
|

Commentary: Update on Animal Models for NTP Studies

Abstract: Based on recommendations of participants at the National Toxicology Program (NTP) workshop "Animal Models for the NTP Cancer Bioassay: Strains and Stocks-Should We Switch?" some modifications to the NTP rodent cancer bioassay were made. The B6C3F1 remains the mouse model used in the cancer bioassay. The use of multiple strains of mice will be explored through a new branch within the NTP, the Host Susceptibility Branch. Several rat models were evaluated; the Harlan Sprague Dawley rat is currently being used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 5 publications
0
35
0
Order By: Relevance
“…Department of Health and Human Services uses this strain in its 2-year studies, after in-depth discussions on the suitability and advantages of the SD rat over previously used strains [23].…”
Section: The National Toxicology Program Of the Usmentioning
confidence: 99%
“…Department of Health and Human Services uses this strain in its 2-year studies, after in-depth discussions on the suitability and advantages of the SD rat over previously used strains [23].…”
Section: The National Toxicology Program Of the Usmentioning
confidence: 99%
“…Consequently, the NTP decided to switch to the Harlan Sprague Dawley (Hsd:Sprague Dawley SD) rat for future bioassays (King-Herbert et al, 2009). Nine previous NTP bioassays had been performed using female Harlan SD rats to evaluate the chronic toxicity and carcinogenicity of dioxins and dioxin-like compounds.…”
Section: Introductionmentioning
confidence: 99%
“…For reproductive toxicity studies in rats, at least 10 live pups per litter is desirable in order to evaluate any adverse effects on fetal development appropriately and therefore the litter size produced by the 8-weekold males was considered inadequate. King-Herbert et al (2010) reported that Wistar Han rats that were time-mated at the animal supplier and then shipped into the National Toxicology Program facility produced small litter sizes (8.2 pups/litter). In the current study, 12-week-old males produced litter sizes >10 pups/litter and there are no concerns for evaluation for the adverse effects on fetuses.…”
Section: Discussionmentioning
confidence: 99%